“Provision of library service to prison inmates in Sri Lanka – a social perspective” - Navaneethakrishnan, S.; Arulanantham, S. (Faculty of Social Sciences, University of Kelaniya, 2013)
The purpose of this research is to shed light on an area of librarianship which is not often talked about in Sri Lankan context i.e. Prison libraries. They aim to provide information that meets the information, recreational, lifelong learning, and transitional needs of prisoners. Around 0.05% of total population of Sri Lanka (11, 381 nos.) was in remand prisons as inmates under the department of prisons. More than 35% prisoners’ average length of time spent on remand was more than six months. The provision of libraries in the various prisons for the inmates’ rehabilitation is non-negotiable. The objective of this research is to identify the need of the provision of library service to prisoners and to emphasis to start the process of a national scheme for library and information service provision to prison inmates in Sri Lanka, based on international recommendations for treatment of prisoners. Based on survey on statistics of current prison system in Sri Lanka, this study emphasizes some significant and basic need of prison libraries. This study reveals that Sri Lanka has to establish prison libraries with at least hundred thousand materials, since IFLA suggests that a prison library should have a collection of ten titles per inmate, Policy decision should be made at national level for prison libraries under the guidance of National Library of Sri Lanka. Bibliotherapic aspects could be implemented for the rehabilitation of prisoners with the support of health sector. As UNESCO stipulates that libraries have an obligation to serve prisoners, public libraries could play vital role in changing the attitude of prisoners by extending their servicers to prisons in the form of mobile libraries and reading camps to enhance access to information and to provide a basis for change of attitude. Awareness also could be created by strengthening prisoners’ information rights by providing library service.
Keywords: Library Science; Prison Libraries; Information Services; Sri Lanka